2020
DOI: 10.1007/s00280-020-04157-2
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclooxygenase activity mediates colorectal cancer cell resistance to the omega-3 polyunsaturated fatty acid eicosapentaenoic acid

Abstract: Purpose The naturally-occurring omega-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) is safe, well-tolerated and inexpensive, making it an attractive anti-cancer intervention. However, EPA has only modest anti-colorectal cancer (CRC) activity, when used alone. Both cyclooxygenase (COX) isoforms metabolise EPA and are over-expressed in CRC cells. We investigated whether COX inhibition increases the sensitivity of CRC cells to growth inhibition by EPA. Methods A panel of 18 human and mouse CRC cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The decreased levels of inflammatory eicosanoids such as leukotriene B4 (LTB4) and prostaglandin E2 (PGE2) have been used to explain how omega-3 FAs have anti-inflammatory properties. Omega-FAs also control the activity of the enzymes cyclooxygenase (COX) and lipoxygenase (LOX) to modify the expression of anti-inflammatory eicosanoids and reduce the creation of inflammatory ones [ 70 ]. For instance, LTB4 is a powerful leukocyte chemoattractant made from arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased levels of inflammatory eicosanoids such as leukotriene B4 (LTB4) and prostaglandin E2 (PGE2) have been used to explain how omega-3 FAs have anti-inflammatory properties. Omega-FAs also control the activity of the enzymes cyclooxygenase (COX) and lipoxygenase (LOX) to modify the expression of anti-inflammatory eicosanoids and reduce the creation of inflammatory ones [ 70 ]. For instance, LTB4 is a powerful leukocyte chemoattractant made from arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…These should include measurement of O3FA levels and parallel mechanistic studies, with which to confirm the validity of any hypothesis underlying post hoc analysis of RCT outcomes according to tumour biomarker stratification 13. A recent in vitro study reported that COX expression by human CRC cells was associated with relative resistance to EPA,90 an observation which is hard to reconcile with the CALGB 89803 finding that high O3FA intake was associated with larger CRC recurrence risk reduction in individuals with COX-2-high tumours 69…”
Section: Do Omega-3 Polyunsaturated Fatty Acids Alter Post-diagnosis ...mentioning
confidence: 99%
“…(R. E. Gupta et al, 2012;Pimentel et al, 2013) EPA and DHA Anti-inflammatory effects through inhibition of nuclear factor kappa-B (NFκB) (Allam-Ndoul et al, 2016;Calder, 2013;Daak et al, 2015;Dang et al, 2017) 20 (Borghi & Cicero, 2006;Filipovic et al, 2018;Jayasooriya et al, 2008;Naini et al, 2015) Cancer EPA Anti-proliferative effects of cancer cells in colorectal cancer. By reducing the level of proinflammatory eicosanoids in prostate cells, the omega-3 PUFAs have the potential to limit cellular damage and reduce the risk for carcinogenesis (R. E. Aucoin et al, 2017;Volpato et al, 2020;C. D. Williams et al, 2011) 21 Sprat (≈17% fat)* 26-37 total PUFA → omega-3 PUFA 22-25.6 → 6.3 EPA+10 DHA (Keinänen et al, 2017;Regulska-Ilow et al, 2013) Salmon (10-13% fat)* 13.5-24.2 total PUFA; n-3 PUFA 0.53-2.4 (0.65 EPA+ 1.8 DHA) (Grahl-Nielsen & Glover, 2010;Linder et al, 2010;Strobel et al, 2012) Sardine (≈14% fat)* 30-49 total PUFA → n-3 PUFA 21-36 → 8.6-18.9 EPA+10.7-32.5 DHA (Bimbo, 2013;De Leonardis & Macciola, 2004;Shirai, 2011) Anchovy (8-16% fat)* 29.6-36 total PUFA → omega-3 PUFA 25.7-31.2 → 9.2-11.6 EPA+ 14.7-19 DHA (Kaya, 2008;ÖKsüz & Özyilmaz, 2010) Conjugated linoleic acid (CLA) Milk 0.7-1.03 total CLA → c9,t11 isomer 75-90% total CLA content (M. Guo, 2009;Kumar et al, 2018;Mushtaq et al, 2010;Rodríguez-Alcalá et al, 2017) Ruminant meat* 0.07-2.97 total CLA Cheese 0.06-1.42 total CLA → 0.14-0.73 c9,t11 isomer →78-84% total CLA content Conjugated linolenic acid (CLNA)…”
Section: Dhamentioning
confidence: 99%